Human Capital Readiness for Digital Transformation in Rural Governance in Indonesia - Is Solikhatun; Teguh Imam Rahayu; Yuli Elfiyanti (CV. Civiliza Publishing, 2026)
Digital transformation in rural governance has become a strategic agenda to improve public service quality, transparency, and administrative effectiveness in Indonesia. Nevertheless, the success of digital transformation is not solely determined by the availability of information technology infrastructure, but is strongly influenced by the readiness of human capital as the main driver of change. This study aims to analyze the readiness of village government human capital in supporting digital transformation in rural governance, using Demak Regency, Central Java, as a case study. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis, and analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the readiness of village apparatus human capital remains at a basic level and is primarily oriented toward administrative compliance rather than strategic digital utilization. Digital competencies, adaptability to technological change, and institutional support have not yet been systematically and sustainably developed. This condition implies that digital transformation in rural governance risks becoming merely an administrative formality if not accompanied by comprehensive human capital development. This study contributes to the digital governance literature by emphasizing the central role of human capital readiness in ensuring effective and sustainable rural digital transformation.